2012
DOI: 10.1007/s10661-012-2670-5
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metal risk assessment for potatoes grown in overused phosphate-fertilized soils

Abstract: The long-term application of phosphate fertilizers on vegetable production fields has raised concerns about the potential health risks of heavy metal contamination of crops grown on contaminated soils in the Hamadan province, western Iran. This study found that long-term fertilizer use led to a growing accumulation of heavy metals in soils. High concentrations of elemental As, Cd, Cr, Cu, Pb, and Zn were found in potatoes sampled from overused phosphate-fertilized soils, which increased the daily intake of met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…It has been observed that the long term use of phosphate fertiliser led to a moderate accumulation of some heavy metals (including lead) and a significant accumulation of cadmium in the soils of Hamadan province in Iran (Cheraghi et al 2013). Cheraghi et al (2013) identified that potatoes grown on heavy metal contaminated soils were contaminated with heavy metals, however, there was not a health risk in eating produce from these soils.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed that the long term use of phosphate fertiliser led to a moderate accumulation of some heavy metals (including lead) and a significant accumulation of cadmium in the soils of Hamadan province in Iran (Cheraghi et al 2013). Cheraghi et al (2013) identified that potatoes grown on heavy metal contaminated soils were contaminated with heavy metals, however, there was not a health risk in eating produce from these soils.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that the long term use of phosphate fertiliser led to a moderate accumulation of some heavy metals (including lead) and a significant accumulation of cadmium in the soils of Hamadan province in Iran (Cheraghi et al 2013). Cheraghi et al (2013) identified that potatoes grown on heavy metal contaminated soils were contaminated with heavy metals, however, there was not a health risk in eating produce from these soils. An additional factor that should be considered is that the concentrations of cadmium and lead should not be taken in isolation, as previously it has been highlighted that the region in which the South-West of Britain survey was conducted had vegetables and fruits with increased concentrations of arsenic (Norton et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Another study done by Tu et al (2000) showed that application of N, P and K fertilisers may change the bioavailability of heavy metals like Pb and Cd present in the soil by changing the soil properties. Chen et al (2008) and Cheraghi et al (2013) highlighted the increase in the trace element concentration in the vegetable cultivated areas due to fertiliser application. The elemental analysis of the samples showed a positive correlation between the fertiliser application and metal concentrations (As, Cd, Pb, P and Zn) in the soil.…”
Section: Fertilisers and Soil Environmentmentioning
confidence: 99%
“…Food consumption is one the most important pathways for human exposure to environmental contaminants (4,6,21,32,34). Heavy metals are released into the environment from natural and human sources such as sewage sludge, municipal solid wastes, metal-based pesticides and fertiliz ers, and industrial emissions (2,15,16,30,32,34).…”
mentioning
confidence: 99%
“…Tubers accumulate metals from the environment through their roots and foliar surfaces. Cadmium (Cd) and lead (Pb) are of particular concern as environmental food contaminants because of their potential toxicity even at low concentrations (2,4). Prolonged exposure to toxic metals such as Cd and Pb can adversely affect human health (18,24).…”
mentioning
confidence: 99%